Exploring CAR T-Cell Dynamics: Balancing Potent Cytotoxicity and Controlled Inflammation in CAR T-Cells Derived from Systemic Sclerosis and Myositis Patients - Dingfelder, Janin; Taubmann, Jule; von Heydebrand, Franziska; Aigner, Michael; Bergmann, Christina; Knitza, Johannes; Park, Soo; Cheng, Joseph K.; Van Blarcom, Thomas; Schett, Georg; Mackensen, Andreas; Lutzny-Geier, Gloria (International Journal of Molecular Sciences, 2025)
Systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and idiopathic inflammatory myositis (IIM) are autoimmune diseases managed with long-term immunosuppressive therapies. Hu19-CD828Z, a fully human anti-CD19 chimeric antigen receptor (CAR) with a CD28 costimulatory domain, is engineered to potently deplete B-cells. In this study, we manufactured Hu19-CD828Z CAR T-cells from peripheral blood of SLE, IIM, and SSc patients and healthy donors (HDs). CAR-mediated, CD19-specific activity of these cells was evaluated in vitro by assessing cytotoxicity, cytokine release, and proliferation assays in response to autologous CD19+ B-cells, the CD19+ NALM-6 B-cell line, or a CD19− U937 non-B-cell line as targets. The results demonstrated an increased proliferation of Hu19-CD828Z CAR T-cells and dose-dependent cytotoxicity against primary autologous and NALM-6 B-cells compared to non-transduced controls or co-cultures with non-B-cells. Notably, autoimmune-patient-derived CAR T-cells produced lower levels of inflammatory cytokines than healthy-donor-derived CAR T-cells in response to CD19+ B-cell targets. These data support the potential of Hu19-CD828Z and its therapeutic cell product KYV-101 as a therapeutic strategy to achieve deep B-cell depletion in SLE, IIM, and SSc patients, and highlights its promise for broader application in B-cell-driven autoimmune disorders.
CRIS-Team Scopus Importer:2025-01-31
Keywords: autoimmune diseases; chimeric antigen receptor; cytokines; idiopathic inflammatory myositis; systemic lupus erythematosus; systemic sclerosis; T-cells